Implementasi Teori 5C Sinematografi dalam Proses Pengambilan Gambar Brand Generated Content (BGC) Akun Tiktok @Kita_Kelana - Karina Adinda Maharani; Abung Supama Wijaya (Journal of Creative Student Research, 2026)
The rapid proliferation of short video comments on TikTok has heightened the importance of visual quality in digital marketing, particularly in creating brand-generated content (BGC) as an authentic and engaging brand communication strategy. This study seeks to elucidate the application of Joseph V. Mascelli’s 5C Cinematography theory, which encompasses Camera Angle, Continuity, Cutting, Close Ups, and Composition, in the production process of BGC content on the TikTok account @kita_kelana. This account serves as a soft-selling communication strategy for the Susu Mbok Darmi brand. Additionally, the study explores the Hybrid Look approach, with data collected through the documentation of seven shotlists and production scripts generated from March to June 2026. The findings indicate that all five elements of the 5C theory were consistently applied throughout the production process of the course. Furthermore, the study identifies the Hybrid Look approach, which integrates static and handheld shots using natural lighting, as a production solution that allows BGC content to appear cinematographic while maintaining authenticity. This study serves as a practical reference for digital content practitioners to produce high-quality BGC on social media platforms.